Halal Tourism Destination from Tourist Perspectives: A Review - Yudha Pamungkas; Dea Latul Inayah Agustin; Fitriani Salsabil Tanisa; Allya Dini Alviana; Dian Nur Anisa; Rachmat Syam; Mega Fitriani Adiwarna Prawira (Journal of Tourism Sustainability, 2023)
Halal tourism has developed as a model for developing tourism destinations amid various existing development approaches. The difference is that halal tourism is formed through an image embedded in a tourism management area that seeks to accommodate the unique needs of Muslim tourists. This study utilizes metadata on Google Scholar and selects 11 papers in the Scopus database to formulate the results of previous studies focusing on halal tourist destinations from visitors' perspectives. From the results of this systematic study, a future research framework is offered where the sustainability of halal tourist destinations can be developed on the management of tourist satisfaction formed by product quality, institutional and social support, and image.